Is one diagnosis the whole story? patients with double diagnoses. Issue 9 (8th June 2016) - Kurolap, Alina; Orenstein, Naama; Kedar, Inbal; Weisz Hubshman, Monika; Tiosano, Dov; Mory, Adi; Levi, Zohar; Marom, Daphna; Cohen, Lior; Ekhilevich, Nina; Douglas, Jessica; Nowak, Catherine Bearce; et al.
Abstract : One of the goals of evaluating a patient in the genetics clinic is to find the diagnosis that would explain his or her clinical presentation. Sometimes the patient's diagnosis remains undefined or does not explain all of the clinical findings. As clinicians are often guided by a "single disorder" paradigm, diagnosing multiple genetic conditions in the same patient requires a heightened sense of awareness. Over the last few years, we evaluated several patients (n = 14) who were found to have more than one genetic diagnosis. In this paper, we will describe their natural history and diagnoses, and draw on the lessons learned from this phenomenon, which we expect to grow in this era of next‐generation diagnostic technologies. To our knowledge, this is by far the largest series of patients with double diagnoses. Based on our findings, we strongly recommend that physicians question every diagnosis to determine whether it indeed explains all of the patients' symptoms, and consider whether they should continue the diagnostic evaluation to look for a more accurate and complete set of diagnoses. © 2016 Wiley Periodicals, Inc.